Analisis Wacana Bias Gender pada Karakter Rhaenyra Targaryen dalam House of the Dragon - Nadhif Arnellyka Putri; Anggian Lasmarito Pasaribu; Alila Pramiyanti (Jurnal Spektrum Komunikasi, 2023)
Gender bias is still an important issue to be discussed at this time. Mass media can be a medium in depicting gender bias, because mass media has the power to influence reality in life. One of the popular mass media in today's society is television series. The television series House of The Dragon is one of the television series that raises the issue of gender bias. This study aims to find out forms of gender bias on the character Rhaenyra Targaryen in the television series House of The Dragon. The research method used is Sara Mills' Critical Discourse Analysis at word level and sentence level. The results of the study found that there is five forms of gender bias in Rhaenyra Targaryen's character, namely (1) stereotypes (2) subordination (3) marginalization (4) double workload and (5) violence. The research results also show that gender bias can occur in women of any status. This research can contribute to the study of gender equality and women.